2008
DOI: 10.1002/jez.b.20251
|View full text |Cite
|
Sign up to set email alerts
|

Role‐reversal of gender‐associated mitochondrial DNA affects mitochondrial function in Mytilus edulis (Bivalvia: Mytilidae)

Abstract: Mussel species of the genus Mytilus possess an unusual system of mitochondrial DNA (mtDNA) transmission termed doubly uniparental inheritance. They are characterized by the presence of two highly divergent gender-associated mtDNA genomes (often with>20 and>10% divergences in DNA and amino acid sequences, respectively) that are inherited either maternally (F mtDNA) or paternally (M mtDNA). Females are typically homoplasmic for the F mtDNA and males are heteroplasmic with the F mtDNA being most common in all tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
48
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 57 publications
5
48
0
Order By: Relevance
“…No. AB055625 and AB055624) (see also [59]). In other mollusks, a relatively small number of mitochondrial genes are transcribed from the second strand.…”
Section: Discussionmentioning
confidence: 99%
“…No. AB055625 and AB055624) (see also [59]). In other mollusks, a relatively small number of mitochondrial genes are transcribed from the second strand.…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons of F and M mtDNA sequences of Mytilus species have shown that the M mitogenome evolves more quickly than the F mitogenome242829. From these studies, it appears that both genomes experience purifying selection, but this selection is relatively relaxed for the M mtDNA in Mytilus spp 24282930…”
mentioning
confidence: 99%
“…According to Melvin et al (2008), an amino acid change is considered likely to affect complex IV activity if its property is changed and/or if the site is in close contact with another subunit. Indeed, substitutions able to modify interactions between nuclear and mitochondrial subunits at positions of structural importance to enzyme function are known to modify enzymatic activity (Barrientos et al, 2000;Melvin et al, 2008;Breton et al, 2009). Therefore, the change at residue 41 on the COX3 mitochondrial subunit could potentially explain the difference of complex IV activity observed between wild type and cybrids.…”
Section: Discussionmentioning
confidence: 94%